Variability of plankton communities in relation to the lunar cycle in oceanic waters - Santiago Hernández-León; M. Loreto Torreblanca; M. Loreto Torreblanca; Inma Herrera; Inma Herrera; Laia Armengol; Gara Franchy; Alejandro Ariza; Juan Carlos Garijo; María Couret (Frontiers in Marine Science)
The short-term variability of plankton communities in the oceanic realm is still poorly known due to the paucity of high-resolution time-series in the open ocean. Among these few studies, there is compelling evidence of a lunar cycle of epipelagic zooplankton biomass in subtropical waters during the late winter bloom. However, there is few information about lower trophic levels and zooplankton physiological changes related to this lunar cycle. Here, we studied the short-term variability of pico-, nano-, micro-, and mesoplankton in relation to the lunar cycle in subtropical waters. Weekly sampling was carried out at four stations located north of the Canary Islands from November 2010 to June 2011. Zooplankton abundance and biomass, gut fluorescence (GF), electron transfer system (ETS), and aminoacyl-tRNA synthetase (AARS) activities were measured before, during, and after the winter vertical mixing in these waters in a wide range of size classes. Chlorophyll a, primary production, and zooplankton biomass were low, showing a rather weak late winter bloom event due to the high temperature and stratification observed. Chlorophyll, nanoplankton, diatoms, and mesozooplankton proxies for grazing (GF), respiration (ETS), and growth (AARS) varied monthly denoting a lunar pattern. Chlorophyll a, nanoplankton, diatoms, and mesozooplankton proxies for grazing and respiration peaked between 4 and 6 days after the new moon, followed by an enhancement of the mesozooplankton index of growth between 8 to 9 days after the new moon. However, mesozooplankton biomass only increased during the productive period when supposedly growth exceeded mortality. Coupled with previous results in pico-, nano-, and microplankton, we suggest that the lunar cycle governs the development of planktonic communities in the high turnover warm subtropical ocean. This study provides further evidence of the match of plankton communities with the predatory cycle exerted by diel vertical migrants, adding essential information to understand the short-term functioning of the open ocean.